Rapid Assessment of Diverse Trichodermal Isolates of Indonesian Origin for Cellulase Production - Fahrurrozi, Fahrurrozi; Ratnakomala, Shanti; Anindyawati, Trisanti; Lisdayanti, Puspita; Sukara, Endang (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2010)
Trichoderma is a well -known candidate to be promoted as cellulase producerÂ for the hidrolysis of lignocelluloses that containÂ inÂ woodyÂ biomass. TheÂ number of trichodermalÂ isolatesÂ in ourÂ laboratory collectedÂ from diverse ecosystem types in Indonesia increases significantly during the last 5 years. It is our aim to assess the cultures for its ability in producing cellulase. Sixty-six trichodermal isolates used in this experiment are obtained from Biotechnology Culture Collection (BTCC), Research Center for Biotechnology, Indonesian Institute of Sciences(LIPI) Â The 31 isolates were isolated from District of Liwa (South Sumatra, Indonesia) and the 35 isolates from District of Maros (South Sulawesi, Indonesia). TheÂ isolates were screened qualitatively,Â 7Â isolatesÂ fromÂ Liwa and 12Â isolates from Maros showed cellulolytic activity. From the results of quantitative test, two strainsÂ (ID08-T004 and ID08-T63) showed the higher cellulolytic activity among the selected strains, 133.5 and 133.5 U/ml, respectively.Â TheseÂ extracellularÂ enzymesÂ wereÂ characterizedÂ theirÂ temperatureÂ andÂ pHÂ optimum.Â The temperatureÂ optimumÂ forÂ bothÂ enzymesÂ wasÂ theÂ same,Â 50ï°C,Â withÂ activityÂ 213.6Â U/mlÂ forÂ enzymeÂ extracted from ID08-T004 and 197.3 U/ml for enzyme from ID08-T0063. The pH optimum was pH 5 of ID08-T004 with activity137.7 U/ml and pH 6 for ID08-T063 with activity 75.0 U/ml. The enzymes from ID08-T004 and ID08-T063 were stable in their temperature and pH optimal condition even after 90 minutes incubation with activity 179.0 U/ml and 86.7 U/ml, respectively. The enzyme stability was approximately 150 minutes for both enzymes in the temperature and pH optimum. Â Key Words: Trichoderma, cellulase, Culture Collection